Does Timing of Coronary Artery Bypass Surgery Affect Early and Long-Term Outcomes in Patients With Non–ST-Segment–Elevation Myocardial Infarction?. Issue 8 (25th August 2015) - Davierwala, Piroze M.; Verevkin, Alexander; Leontyev, Sergey; Misfeld, Martin; Borger, Michael A.; Mohr, Friedrich W.
<x xml:space="preserve">Abstract</x> Background— Current guidelines do not provide recommendations for optimal timing of coronary artery bypass surgery (CABG) in patients with non–ST-segment–elevation myocardial infarction. Our study aimed to determine the impact of CABG timing on early and late outcomes in patients with non–ST-segment–elevation myocardial infarction. Methods and Results— A total of 758 patients underwent CABG within 21 days after non–ST-segment–elevation myocardial infarction between January 2008 and December 2012 at our institution. The patients were divided into 3 groups according to the time interval between symptom onset and CABG: group A, <24 hours (133 patients); group B, 24 to 72 hours (192 patients); and group C, >72 hours to 21 days (433 patients). Predictors of in-hospital and long-term mortality were identified by logistic and Cox regression analyses, respectively. Overall in-hospital mortality was 5.1% (39 patients): 6.0%, 4.7%, and 5.1% in groups A, B, and C (P=0.9), respectively. A total of 118 patients died during follow-up. The 5-year survival was 73.1±2%, with a nonsignificant trend toward better survival in groups A (78.2±4%) and C (75.4±3%) compared with group B (63.6±5%; log-rank P=0.06). Renal insufficiency and LMD were independent predictors of in-hospital (odds ratio, 3.1; P=0.001; and odds ratio, 3.1; P=0.002) and long-term mortality (hazard ratio, 1.7; P=0.004; and hazard ratio, 1.5; P=0.02), whereas administration of P2Y12 inhibitors was protective (odds ratio, 0.3; P=0.01). Conclusions— Emergent CABG within 24 hours of non–ST-segment–elevation myocardial infarction is associated with in-hospital mortality and long-term outcomes similar to those of CABG performed after 3 days, despite a higher risk profile. CABG performed between 24 to 72 hours showed a nonsignificant trend toward poorer long-term outcomes. Dual antiplatelet therapy until surgery is beneficial, whereas renal insufficiency and left main disease increase the risk of early and late death.